The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0251301
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions about antibiotic use and antimicrobial resistance among final year undergraduate medical and pharmacy students at three universities in East Africa

Abstract: Introduction Proper measures to combat antimicrobial resistance development and spread in Sub Saharan Africa are very crucial bearing in mind the projected burden of antimicrobial resistance which is expected to be increase by 2050. Training of medical doctor and pharmacy students in antimicrobial stewardship is vital to combat antimicrobial resistance. This study was designed to evaluate the knowledge, attitude, and perception of final year medical and pharmacy students on antimicrobial use and antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 24 publications
5
35
4
Order By: Relevance
“…Our study respondents were well prepared regarding certain activities of stewardship programs, including infectious disease diagnosis and initiation of antibiotic therapy coupled with dosing, which is in line with previous studies conducted on South and East African medical students ( Wasserman et al, 2017 ; Lubwama et al, 2021 ). Nonetheless, students lacked preparedness regarding knowledge of the spectrum of antibiotics and proper antibiotic selection, which are integral components of judicial antibiotic prescribing.…”
Section: Discussionsupporting
confidence: 81%
“…Our study respondents were well prepared regarding certain activities of stewardship programs, including infectious disease diagnosis and initiation of antibiotic therapy coupled with dosing, which is in line with previous studies conducted on South and East African medical students ( Wasserman et al, 2017 ; Lubwama et al, 2021 ). Nonetheless, students lacked preparedness regarding knowledge of the spectrum of antibiotics and proper antibiotic selection, which are integral components of judicial antibiotic prescribing.…”
Section: Discussionsupporting
confidence: 81%
“…As has been demonstrated in other studies, there are gaps in the practical skills of final-year medical students in crucial topics addressing antimicrobial resistance, antimicrobial stewardship, and IPC. 45 Similarly, lack of awareness of IPC programs/guidelines in the hospital may reflect the state of IPC program in the teaching hospital in general. A study at Lira University Hospital showed that the IPC compliance level was basic with no IPC committee, no IPC team, no IPC training for the health workers at the hospital, and no IPC surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…That is why various methods meant to improve physicians’ knowledge and decision-making patterns, considering indications for antibiotic therapy, its goals, benefits and side effects, have been so important [ 6 , 41 , 42 , 43 ]. Already during their studies, young adepts of medicine across the world have the opportunity to familiarize themselves with specific recommendations for the treatment of most common infections, such as those affecting the respiratory system or genitourinary tract [ 44 , 45 , 46 , 47 ]. Clinical practice guidelines certainly facilitate making decisions on the choice of a specific antibiotic regimen.…”
Section: Discussionmentioning
confidence: 99%